FUN AND ENGAGING MATHEMATICS LEARNING THROUGH THE 'GO FUN' MEDIA FOR JUNIOR HIGH SCHOOL STUDENTS IN RUHUI RAHAYU VILLAGE - Rahayu, Setia Widia (Universitas Muhammadiyah Aceh, 2025)
Nowadays, mathematics learning is becoming less favored by students, as mathematics is often considered the most difficult subject to understand. In fact, we know that almost all aspects of life involve mathematical knowledge. Based on several interviews conducted with junior high school students in Ruhui Rahayu Village, nearly 60% of students stated that they did not like mathematics, and their exam scores in this subject were below the minimum passing grade (KKM). As an educator, I felt challenged to carry out a community service program related to mathematics learning for these junior high school students in Ruhui Rahayu Village. From the community service activities we conducted, it turned out that the students' abilities in geometry (specifically in solid figures) showed improvement. Additionally, the students developed a greater interest in learning mathematics. Teaching mathematics using the